FRI0091 A STUDY OF THERAPEUTIC PREFERENCES IN RHEUMATOID ARTHRITIS AFTER FAILURE OF A FIRST-LINE STRATEGY INCLUDING METHOTREXATE, USING THE DISCRETE CHOICE EXPERIMENTS METHODOLOGY. (2nd June 2020) - Senbel, E.; Durand, F.; Roux, B.; Badaoui, F. Z.; Fautrel, B.
Abstract : Background: Therapeutic decisions in patients with rheumatoid arthritis (RA) who have an inadequate response to methotrexate (MTX-IR) are complex. European guidelines position at the same level all biological disease-modifying anti-rheumatic drugs (bDMARDs) and targeted synthetic DMARDs (tsDMARDs) for the treatment of RA (1, 2) . Furthermore, therapeutic decisions, or physician preferences, may be influenced by many factors related to patients and/or physicians. Objectives: To describe the therapeutic preferences of physicians involved in the management of RA after failure of a first-line strategy (including MTX) and the influence of predefined factors on these preferences. Methods: We planned to include 216 rheumatologists experienced in the management of RA in this cross-sectional multicenter study. A total of 64 hypothetical clinical cases (vignettes) were developed from a random combination of the following parameters: presence or absence of poor prognostic factors 1) RA-related autoantibodies, 2) structural damage progression on X-ray, 3) high or moderate disease activity, and presence or absence of a history of 4) infection, 5) pulmonary involvement, and 6) cardiovascular disease. Each participant was asked to complete 8 vignettes and were asked to choose the most and least appropriate therapeutic option (best-worst [BW] scaling method) from 3 of the following: replacing MTX by another conventional (c)sDMARD; adding one or more csDMARDs to MTX; adding a bDMARD (TNF inhibitor [TNFi], tocilizumab [TCZ], abatacept [ABA] or rituximab [RTX]). Each vignette was completed 10 times per participant. Physician preferences were assessed using discrete choice experiments methodology. Therapeutic option preference was expressed using a score – one point incremented when considered most appropriate; or removed when considered least appropriate. The therapeutic score was standardized for each vignette, ranging from -1 (more often chosen as the least appropriate) to +1 (more often chosen as the most appropriate). A normalized Best-to-Worst (BW) Score was then computed. The multiplication of vignettes and therapeutic options were used to elicit participants' preferences without directly asking them to state their preferred options (3, 4, 5) . Statistical analyses were carried out using SAS (version 9.4), or R (version 3.5.1). Results: A total of 211 French rheumatologists were recruited. Half of them had a hospital-only activity, 25% office-only activity and the rest had mixed activity. Each vignette was assessed by between 20 and 28 rheumatologists with a 94% completion rate. TNF inhibitors were the strategy of choice in 80% of the vignettes. ABA was the second preferred strategy in 75% of the vignettes; except in the 20% of patients with a history of infection and pulmonary comorbidity where it was the first choice. TCZ was chosen as a third strategy. All other strategies were associated with a negative BW score. Factors related to the prescribing physician appear to have no or only a limited impact on therapeutic decisions. Conclusion: This study provides information on the prescription habits of French rheumatologists in MTX-IR patients in RA, and reveals a conservative trend with TNFi the main therapeutic choice and ABA for patients with pulmonary involvement or high risk of infection. The study should be repeated in the future to include new therapeutic options. References: [1]Smolen J et al., EULAR 2019 [2]Daien C et al., Joint Bone Spine 2019 [3]Peabody JW et al., JAMA 2000 [4]Fautrel et al., Arthritis Rheum 2009 [5]Mühlbacher et al. Health Economics Review 2016 Disclosure of Interests: Eric Senbel Consultant of: Nordic, Roche-Chugai, Lilly, Abbvie, Amgen, Pfizer, Sanofi, MSD, Biogen, UCB, frederick durand Shareholder of: Eli Lilly, Employee of: Lilly France, Baptiste Roux Grant/research support from: FAST4 company has received funding for research from Lilly, Pfizer, BMS, Vifor Pharma, Amgen, Novartis, Leo Pharma, Sanofi, Baxter, Abbvie, Astrazeneca, Novonordisk and Hac Pharma., Fatima Zohra Badaoui Employee of: Lilly France, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant of: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Lilly, Janssen, Medac MSD France, Nordic Pharma, Novartis, Pfizer, Roche, Sanofi Aventis, SOBI and UCB